DEBU DAN KAPASITAS PARU MASYARAKAT DI SEKITAR PROYEK REHABILITASI DAS TONDANO DI KELURAHAN KARAME - Bongakaraeng Bongakaraeng; Aulia T. Moo; Suwarja Suwarja (POLTEKKES KEMENKES MANADO, 2019)
The Tondano watershed rehabilitation project is a project that consists of the construction of embankments and roads along the Tondano river. This project activity can cause air pollution, which has the potential to affect the occurrence of public health problems, especially the occurrence of lung capacity disorders. From the results of the preliminary service, it was found that some people complained of frequent coughing, runny nose and shortness of breath. Based on this fact, research was conducted on the effect of dust on the disruption of the lung capacity of the community. This research is a descriptive study. The samples in this study were 26 people. The instrument used to measure lung capacity is a spirometer. The variables studied were Das Tondano Rehabilitation Project Dust levels and Lung Capacity. The results showed that the level of dust in the study area around the Das Tondano rehabilitation project site in Environment 4 of Karame Sub-district was the value of dust content at point I 266 μg / m3, point II 644 μg / m3, point III 488 μg / m3. Average value of 466 µg / m3. above the PP 41/2009 quality standard of 230 μg / m3. From the measurement of lung capacity, the incidence of lung capacity is 4 people (15.4%). In the project initiator to carry out regular ambient air quality monitoring around the Das Tondano rehabilitation project and efforts to control air pollution by carrying out road pollution every day.